Problematika Penyaluran Bantuan Langsung Tunai Dana Desa (BLT DD) Tahun 2020 - Suryaningsih Aseh; Tengku Fahrul Gafar; Zamhasari Zamhasari (JOELS: Journal of Election and Leadership, 2021)
The priority for using the Village Fund in 2020 has changed along with the existence of financial policies for handling the dissemination of COVID-19 in the village. Based on this, the Village Fund (DD) is prioritized used for handling the COVID-19, one of the priorities is for Direct Cash Assistance (BLT). In its implementation, the Direct Cash Assistance of the Village Fund (BLT-DD) policy has caused many polemics. Based on these problems, the purpose of this paper is to explore the factors that influence the implementation performance of BLT DD distribution. The method used in this research is qualitative exploratory. Data collection was conducted by means of observation, interviews, and literature study. The results displayed that the factors affecting the implementation performance were caused by; first, the factor of clarity of policy content, village volunteers found it difficult to collect data on BLT-DD Beneficiary Families (KPM) due to the criteria set fluctuated and the number of KPM was limited based on the percentage of The Village Funds received by the village. The second, the Regulatory Inconsistency Factor. The changing regulations made it difficult for the village government to implement the BLT-DD distribution. Third, technical factors. The process of disbursing the BLT-DD was long enough to prevent The Village Government from delivering BLT-DD on time.